Relationship between disease severity and myeloperoxidase in chronic viral hepatitis: a prospective study - Senol, Arzu; Balin, Safak O. (Future Medicine Ltd, 2023)
Aim: To measure serum myeloperoxidase (MPO) levels and to evaluate the relationship between this parameter and histological findings in chronic hepatitis B and C patients. Materials & methods: Three groups were formed: chronic hepatitis B, chronic hepatitis C and a control group. Serum MPO levels were determined by ELISA. Results: MPO level was found to be higher in both patient groups compared with the control group (p < 0.05). It was also higher in chronic hepatitis B and C patients with significant fibrosis compared with patients with mild fibrosis (p < 0.05). Conclusion: Our results show that increased MPO level can be used as an important noninvasive marker in both the early detection of liver fibrosis and the prediction of significant fibrosis.
Keywords: chronic hepatitis B; chronic hepatitis C; myeloperoxidase